Importance of two-dimensional cation clusters induced by protein folding in intrinsic intracellular membrane permeability. Issue 8 (21st July 2022) - Negi, Shigeru; Hamori, Mami; Kawahara-Nakagawa, Yuka; Imanishi, Miki; Kurehara, Miku; Kitada, Chieri; Kawahito, Yuri; Kishi, Kanae; Manabe, Takayuki; Kawamura, Nobuyuki; Kitagishi, Hiroaki; Mashimo, Masato; et al.
Abstract : Two-dimensional cation clusters formed on the surface of proteins play an important role in their intracellular translocation. Abstract : We investigated the cell penetration of Sp1 zinc finger proteins (Sp1 ZF) and the mechanism via which the total cationic charge and distribution of cationic residues on the protein surface affect intracellular trafficking. Sp1 ZFs showed intrinsic cell membrane permeability. The intracellular transfer of Sp1 ZFs other than 1F3 was dependent on the total cationic charge. Investigation of the effect of cationic residue distribution on intracellular membrane permeability revealed that the cellular uptake of unfolded Zn 2+ -non-coordinating Ala mutants was lower than that of the wild type. Therefore, the total cationic charge and distribution of cationic residues on the protein played crucial roles in intracellular translocation. Mutational studies revealed that the two-dimensional cation cluster on the protein surface significantly improved their cellular uptake. This study will contribute to the design of artificial cargoes that can efficiently transport target substances into cells.